A novel bispecific antibody dual-targeting approach for enhanced neutralization against fast-evolving SARS-CoV-2 variants - Kim, Ji Woong; Kim, Hyun Jung; Heo, Kyun; Lee, Yoonwoo; Jang, Hui Jeong; Lee, Ho-Young; Park, Jun Won; Cho, Yea Bin; Lee, Ji Hyun; Shin, Ha Gyeong; Yang, Ha Rim; Choi, Hye Lim; et al. (Frontiers in Immunology, 2023)
The emergence of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants has caused unprecedented health and socioeconomic crises, necessitating the immediate development of highly effective neutralizing antibodies. Despite recent advancements in anti-SARS-CoV-2 receptorbinding domain (RBD)-specific monoclonal antibodies (mAbs) derived from convalescent patient samples, their efficacy against emerging variants has been limited. In this study, we present a novel dual-targeting strategy using bispecific antibodies (bsAbs) that specifically recognize both the SARS-CoV-2 RBD and fusion peptide (FP), crucial domains for viral attachment to the host cell membrane and fusion in SARS-CoV-2 infection. Using phage display technology, we rapidly isolated FP-specific mAbs from an established human recombinant antibody library, identifying K107.1 with a nanomolar affinity for SARS-CoV-2 FP. Furthermore, we generated K203.A, a new bsAb built in immunoglobulin G4-(single-chain variable fragment)2 forms and demonstrating a high manufacturing yield and nanomolar affinity to both the RBD and FP, by fusing K102.1, our previously reported RBD-specific mAb, with K107.1. Our comprehensive in vitro functional analyses revealed that the K203.A bsAb significantly outperformed the parental RBD-specific mAb in terms of neutralization efficacy against SARS-CoV-2 variants. Furthermore, intravenous monotherapy with K203.A demonstrated potent in vivo neutralizing activity without significant in vivo toxicity in a mouse model infected with a SARS-CoV-2 variant. These findings present a novel bsAb dual-targeting strategy, directed at SARS-CoV-2 RBD and FP, as an effective approach for rapid development and management against continuously evolving SARS-CoV-2 variants.